1967
DOI: 10.1002/jlac.19677060118
|View full text |Cite
|
Sign up to set email alerts
|

Über natürliche Gerbstoffe, XXXVII. Hexahydroxy‐diphensäure (Ellagsäure), Brevifolin‐carbonsäure und Chebulsäure als Umwandlungsprodukte der Brevilagine und des Terchebins

Abstract: Das Auftreten von Ellagsaure (7) und Brevifolin-carbonsaure (9) bei der Hydrolyse des Brevilagins 1 findet eine gute Erklarung durch die ,,Redox-Disproportionierung vicinaler Polycarbonylverbindungen". Auch beim Erhitzen der Brevilagine mit Wasser oder Acetatpuffer werden diese Sauren nachgewiesen. Brevifolin-carbonsaure entsteht auch aus Terchebin beim Erhitzcn mit Acetatpuffer. Bei der Behandlung des Terchebins und wahrscheinlich auch der Brevilagine mit Natronlauge entsteht neben der Brevifolin-carbonsaure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Evidence for enediol intermediacy followed from isolation of oxygen-sensitive dihydrogallic acid (Scheme ) along with protocatechuic acid in respective yields of 54% and 36% from an anaerobic, K 2 HPO 4 (1 M) solution of DHS stirred for two days at rt. These reaction conditions differ markedly from the high pressure, Raney nickel hydrogenation of sodium gallate previously used to synthesize dihydrogallic acid . Based on the observation (Figure B) that the dihydrogallic acid/protocatechuic acid product ratio was displaced in favor of dihydrogallic acid by increasing the concentration of inorganic phosphate, DHS was reacted with 4 M Na 1.5 H 1.5 PO 4 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence for enediol intermediacy followed from isolation of oxygen-sensitive dihydrogallic acid (Scheme ) along with protocatechuic acid in respective yields of 54% and 36% from an anaerobic, K 2 HPO 4 (1 M) solution of DHS stirred for two days at rt. These reaction conditions differ markedly from the high pressure, Raney nickel hydrogenation of sodium gallate previously used to synthesize dihydrogallic acid . Based on the observation (Figure B) that the dihydrogallic acid/protocatechuic acid product ratio was displaced in favor of dihydrogallic acid by increasing the concentration of inorganic phosphate, DHS was reacted with 4 M Na 1.5 H 1.5 PO 4 .…”
Section: Resultsmentioning
confidence: 97%
“…The hydrate of dihydrogallic acid melted 181−2 °C (dec). After vacuum drying these crystals melted 191.5−192.5 °C (lit 6a. mp 192−3 °C, dec); 1 H NMR (1.2M P i , TSP, δ = 0 ppm) 2.70 (dd, J = 17, 8 Hz, 2H), 2.65 (dd, J = 17, 6 Hz, 2H), 2.94 (m, lH); 13 C NMR (H 2 O/D 2 O, 1,4-dioxane, δ = 70.0 ppm) 180.5, 179.7, 133.6, 40.8, 36.8; IR (mineral oil mull, cm -1 ) 3610 (w), 3425 (m), 1706 (m), 1665 (m), 1551 (s), 1319 (s), 1238 (s), 1210 (m), 1158 (s), 1020 (m) 962 (m); HRMS (EI) calcd.…”
Section: Methodsmentioning
confidence: 99%
“…The DHHDP ester group of 12 was alternatively contracted to a brevifolincarboxyl group ( 31 ) attached at the glucose 4-position (cf. section II.B), in 33% yield upon treatment with triethylamine in acetonitrile (Scheme ). 5n, This brevifolyl ester group is found, inter alia , in the ellagitannins repandusinin ( 28 ) 5m (Schemes and ) and heterophylliin E …”
Section: Further Modificationsmentioning
confidence: 96%
“…Typical examples of this subfamily are the crystalline chebulinic and chebulagic acids ( 26 and 14 ), 3g,13b-c,, and repandusinic acid A ( 27 ),5m which features a dehydrochebuloyl group at the 4-position of β-1-galloyl-3,6-( R )-(hexahydroxydiphenoyl)- d -glucose (Scheme ). The structural relationship between chebulic acyl and hexahydroxydiphenic acyl groups was first recognized by Schmidt, who suggested that in vivo hydrolytic cleavage of one aromatic ring of a presumed 2,4-HHDP bearing precursor might provide the biogenetic link to the chebuloyl esters. ,3g Interestingly, geraniin ( 12 ) is converted into 27 in 17% yield upon brief treatment with aqueous sodium hydroxide (Scheme ). 5n, The formation of chebuloyl ( 33 ) moieties through the intermediacy of naturally occurring 2,4-DHHDP ester groups could also have some biosynthetic relevance (Scheme ).
11
12
…”
Section: Further Modificationsmentioning
confidence: 99%
“…In those days, no ellagitannin containing structure 68 had been found. On the other hand, it was known that the hydrolysis of terchebin and brevilagins ( 58 and 69 ) [ 28 ], which had been considered to have the iso -HHDP and DHHDP groups, respectively, produced ellagic acid and 68 [ 63 ]. In addition, a method for the discrimination of the DHHDP and iso -HHDP groups had been known [ 52 ], which was that the treatment of dehydrohexahydroxydiphenic acid ( 70 ) with concentrated hydrochloric acid precipitated 59 out, but the treatment of 71 did not result in the same outcome.…”
Section: Structural Revision In Ellagitanninsmentioning
confidence: 99%